2009
DOI: 10.1136/pgmj.2008.072678
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of breast self examination in a group of women in Shiraz, southern Iran

Abstract: Considering that 46.7% of participants did not perform BSE, and that almost all of those who did perform BSE did it incorrectly-and taking into account that a lack of knowledge on how to perform BSE was the main reason why most non-performers did not examine themselves-establishing educational programmes to teach women at risk may help in the early diagnosis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…For example, a study by Simi et al (2009) found out that 43% of Iranian women’s self-breast examination behavior is explained by their attitudes alone; where by 9% of the women indicated that they do not perform breast self-examination out of fear of a positive outcome, and 34% perceived breast self-examination as useless and unnecessary. Along the same lines, Lamyian et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Simi et al (2009) found out that 43% of Iranian women’s self-breast examination behavior is explained by their attitudes alone; where by 9% of the women indicated that they do not perform breast self-examination out of fear of a positive outcome, and 34% perceived breast self-examination as useless and unnecessary. Along the same lines, Lamyian et al .…”
Section: Discussionmentioning
confidence: 99%
“…3,[13][14][15] This study has been carried out among 400 health professionals of tertiary care hospital of central India with basic intention to see the seriousness of health professionals themselves about BSE.…”
Section: Discussionmentioning
confidence: 99%
“…A note on the software program for statistical analyses should be accompanied by detailed descriptions of how various variables were analyzed and presented. An example of the acceptable note reads as (1):…”
Section: Statistical Analyses Sectionmentioning
confidence: 99%